THE EFFECTIVENESS OF SOCIALIZATION GROUP ACTIVITY THERAPY (TAKS) ON DEPRESSION IN THE ELDERLY IN GAMPONG KEURAMAT, KUTA ALAM DISTRICT, KOTA BANDA ACEH, IN 2022 - Jannah, Miftahul; Laila, Nurnarita; Damayanti, Ira; Yenni, Manovri; Mutia, Sri Alna (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: Based on 2021 Ministry of Home Affairs data, there are 418.156 elderly people in Aceh Province. BPS data for Kota Banda Aceh in2021 shows that there are 55.504 elderly people, and 1,041 elderly people are in Gampong Keuramat, Kuta Alam District, Kota Banda Aceh. Objective: This study aims to determine the effectiveness of Social Group Activity Therapy (TAKS) on depression in the elderly in Gampong Keuramat, Kuta Alam District, Kota Banda Aceh. Method: This research is a Pre-Experimental Design. The population in this study were all elderly people who lived in Gampong Keuramat, Kuta Alam District, Kota Banda Aceh, totaling 1,041 people. The research sample was taken using the Accidental Sampling Technique. Data analysis used the statistical test of the Paired One Sample t-Test and the Chi-square test. Results: The results of the study showed that there was a difference between before and after carrying out Social Group Activity Therapy (TAKS) on depression in the elderly with a value of sig. (2-tailed)=0.000. The results of statistical tests using Chi-square also show that there is a relationship between the history of chronic disease (p-value:0.010) and family income (p-value:0.048) with depression in the elderly in Gampong Keuramat, Kuta Alam District, Kota Banda Aceh. Recommendation: It is recommended that health workers can further increase the role of Posyandu for the elderly, and also cross-sectoral cooperation, especially cooperation in improving the health status of the elderly, and minimizing diseases that occur in the elderly, as well as being more active in inviting the elderly to utilize the health facilities to maintain the health of the elderly.